Bioconcentration of carbamazepine, enalapril, and sildenafil in neotropical fish species - Rojo, Macarena Gisele; Cristos, Diego; Carriquiriborde, Pedro (Frontiers in Toxicology, 2023)
Sewage effluents are the main source of entry of Human Pharmaceutical Active Ingredients (HPAIs) to surface water bodies. Carbamazepine (CBZ), psychiatric drug, enalapril (ENA) antihypertensive, and sildenafil (SIL), to treat erectile dysfunction, have been frequently detected in receiving wastewater and in wild fish species from Argentina. This study aimed to assess the bioconcentration of selected HPAIs in native fish species of the Del Plata Basin. In a first trial, the bioconcentration factors of CBZ, ENA, and SIL were obtained by exposing Cnesterodon decemmaculatus, respectively, to 135, 309, and 70 μg/L during 96 h. Then the bioconcentration kinetic of SIL was comparatively assessed in C. decemmaculatus and Piaractus mesopotamicus exposed, respectively, to 44.1 and 16.2 μg/L during a one-week, followed by a four-day depuration phase. HPAIs concentrations in water and tissue were measured by HPLC-MS after 0.22 μm filtration and direct injection or solid-liquid extraction, respectively. Bioconcentration factors obtained empirically (BCFe) for C. decemmaculatus were CBZ = 1.5, SIL = 1.4, and ENA = 0.007. Parameters estimated by the SIL bioconcentration kinetic model for C. decemmaculatus were: uptake rate constant (k1) = 5.5 L/kg d, elimination rate constant during uptake phase (k2u) = 0.00175 d−1, maximum predicted tissue concentration (Ct(max)) = 138588 μg/kg, estimated bioconcentration factor (BCFm) = 3143, lag time between the exposure and the first detection in tissue (tlag) = 0 d, elimination rate constant in the depuration phase (k2d) = 0.49 d−1 and half-life in the tissue (t1/2) = 1.4 d. The model parameters for P. mesopotamicus were k1: 7.3 L/kg d, k2u: 0.0836 d−1, Ct(max): 1423 μg/kg, BCFm: 88, tlag: 3.8 d in the uptake phase and k2d: 0.31 d−1 and t1/2: 2.3 d in the depuration phase. The reached conclusions were: 1) the bioconcentration capacity of CBZ and SIL are similar but around 200 times higher than ENA, 2) the time to reach the bioconcentration equilibrium for SIL is longer than 1 week, then estimated BCFm are between 1 and 3 orders of magnitude higher than BCFe obtained after 96 h exposure, but actual values need to be verified, 3) substantial differences (≈30 fold) were observed in the estimated BCF of SIL among species, indicating the need for further studies toward understanding such diversity to improve HPAIs ecological risk assessment worldwide.